2010
DOI: 10.2343/geochemj.1.0093
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and diurnal changes of low molecular weight organic acids and ^|^alpha;-dicarbonyls in suburban aerosols collected at Mangshan, North China

Abstract: Aerosol samples were collected at Mangshan in the north of Beijing, China in autumn 2007 and analyzed for α,ω-dicarboxylic acids (C 2 -C 12 ), ketoacids (ωC 2 -ωC 4 , ωC 9 , pyruvic acid) and α-dicarbonyls (glyoxal and methylglyoxal). Oxalic (C 2 ) acid was found as the most abundant species, followed by succinic (C 4 ) and malonic (C 3 ) acids. Concentrations of most compounds, except for C 2 and some other species, were higher in daytime than nighttime, indicating that diacids are produced by photochemical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
2
12
2
Order By: Relevance
“…These observations are consistent with the diurnal distributions of glyoxylic acid in the time-resolved aerosols from Tokyo, whose concentrations showed a positive correlation with ambient temperature and ozone (Kawamura and Yasui, 2005). In the late afternoon or night to early morning, when relative humidity increases, ωC 2 can be oxidized to oxalic acid possibly in the aerosol aqueous phase (Warneck, 2003;Miyazaki et al, 2009;He and Kawamura, 2010).…”
Section: Compositional Changes Of Dicarboxylic Acidssupporting
confidence: 75%
“…These observations are consistent with the diurnal distributions of glyoxylic acid in the time-resolved aerosols from Tokyo, whose concentrations showed a positive correlation with ambient temperature and ozone (Kawamura and Yasui, 2005). In the late afternoon or night to early morning, when relative humidity increases, ωC 2 can be oxidized to oxalic acid possibly in the aerosol aqueous phase (Warneck, 2003;Miyazaki et al, 2009;He and Kawamura, 2010).…”
Section: Compositional Changes Of Dicarboxylic Acidssupporting
confidence: 75%
“…Although the differences in the ratios are not significant, wetter conditions under strong solar radiation may enhance the photochemical aging of organic aerosols in the tropical atmosphere. Based on the filed experiments, aqueous aerosol phase production of oxalic acid was reported in urban and suburban sites (Miyazaki et al, 2009;He and Kawamura, 2010). However, when compared to literature values, our C 3 /C 4 ratios are slightly lower than those (1.5) reported in Tokyo (Kawamura and Ikushima, 1993) and 1.4 in Chennai but comparable to those (0.84) in Nainital, India (Hegde and Kawamura, 2012) and those (1.3) in Jeju Island in the East China Sea .…”
Section: Comparison Of Molecular Composition Of Diacids and Related Ccontrasting
confidence: 53%
“…He and Kawamura (2010) have shown that nighttime observations of oxalic acid over polluted areas are about 1.3 times higher than the daytime ones. However, most of the data used for Fig.…”
Section: Comparison With Observationsmentioning
confidence: 99%